Pemberdayaan masyarakat dalam peningkatan gizi balita melalui olahan produk berbasis pangan lokal jagung di Desa Mekarjaya - Listyaningrum, Ratna Sari; Anggraeni, Angga; Rianti, Fahrisa; Fadillah, Ismatul; Wulandari, Dinda; Hasanah, St Nurul (INDRA: Jurnal Pengabdian kepada Masyarakat, 2024)
Nutritional problems can hinder the momentum of development of Indonesia's golden generation in 2045. Nutritional problems are also related to the availability of food, where local food that is high in nutrients can be used to fulfill the nutrition of children under five. The local food commonly grown in Mekarjaya Village is corn. Therefore, this community service aims to increase the understanding of posyandu cadre mothers and parents of PAUD students regarding the importance of toddler nutrition and provide insight regarding the processing of local corn-based food products. The methods used are observation, lecture, discussion and demonstration. The activity was held on August 28 2023 with 17 participants, namely posyandu cadres and parents of PAUD students. The material is delivered by expert. The demonstration was carried out by providing a practical guide to processing corn into corn juice, corn pudding and corn dregs nuggets. From the results of the activity satisfaction questionnaire, it was found that the time for organizing the activity, preparation and media used were good. The participants were satisfied with the method and clarity of the material.